Answer:
(1, 6)
(7, 0)
Step-by-step explanation:
y = -x + 7
y = -0.5(x - 3)² + 8
-x + 7 = -0.5(x - 3)² + 8
-x + 7 = -0.5(x² - 6x + 9) + 8
-x + 7 = -0.5x² + 3x - 4.5 + 8
0 = -0.5x² + 4x - 3.5
0 = x² - 8x + 7
0 = (x - 7)(x - 1)
x - 7 = 0 or x - 1 = 0
x = 1 or 7
Answer:
<h2>C. 153</h2>
<em>Hope</em><em> this</em><em> helps</em>
<em>shshsgshsh</em>
Answer:
5
Step-by-step explanation:
the base is the original number which you perform an action on. in this scenario the action is 3. 5 is being cubed
If z represents the variable of the standard normal distribution curve N(0,1), which is symmetrical about z=0, then we look for
P(z)-P(-z)=0.9642=1-2P(-z) => P(-z)=(1-0.9642)/2=0.0179
=>
-z=-2.099192
=> z=2.099192
Check:
P(2.099192)-P(-2.099192)=0.9642 ok
22 miles,
30miles - 8 miles = 22 miles
Mikes trip to work is 22 miles farther than sam’s